Ten-year survival in glioblastoma. A systematic review - Tykocki, Tomasz; Eltayeb, Mohamed (Journal of clinical neuroscience, 2018)
•This is the largest cumulative descriptive study to date on the 10-year survival in GBM.•The 10-year survival rate in the population with GBM is established 0.71%.•OS was positively correlated with the length of PFS and inversely related with age at diagnosis. Glioblastoma (GBM) is among the most deadly neoplasms associated with one of the worst 5-year overall survival (OS) rates among all human cancers. The aim of this systematic review is to present all cases with OS of a decade or more and to perform a descriptive analysis of the group. This systematic review was conducted in compliance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline. A comprehensive search for relevant articles was performed on PubMed, Embase and Google Scholar for a period until June 10, 2016, using the following search words: glioblastoma multiforme, glioblastoma, GBM, long-term survival/survivors. Reports containing cases with the long-term survival of 10 years or longer were included in the review. The search produced 36 studies with 162 cases published in the years 1950–2014. The rate of long survivors in the cohort studied was established 0.76%. Mean age at diagnosis, OS and PFS were 31.1 ± 11.1, 15.9 ± 6.3, 11.9 ± 5.6 years respectively. Total and subtotal resections were found in 82 and 58 patients respectively. Nine cases received a biopsy alone. No statistical differences were found in a comparison of PFS, OS and age between total and subtotal resection groups. A regression analysis showed a significant correlation between PFS and OS, with an inverse relationship stated between age at diagnosis and OS. The 10-year survival rate in the cohort studied with GBM was estimated 0.71%. OS was positively correlated with the length of PFS and inversely related with age at diagnosis.